Developing a Hybrid of Suggestopedia and Total Physical Response (TPR) to Enhance English Vocabulary Mastery in Elementary Learners - Sibarani, Imelda Sabrina; Simarmata, Radode Kristanto; Tindaon, Tria Margaretha (International Journal of Contemporary Studies in Education, 2025)
Purpose – This study investigates the effectiveness of combining Suggestopedia and Total Physical Response (TPR) methods to enhance English vocabulary acquisition in elementary learners using a Pocket English Dictionary. The research aims to address the limited vocabulary proficiency among young learners by integrating psycholinguistic and kinesthetic approaches in a tangible format. Methodology – The research utilized a modified Borg and Gall development design with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). A purposive sampling method selected 25 sixth-grade students from State Elementary School 091550 in Rajamaligas. Data were collected through observations, interviews, questionnaires, and pre- and post-tests, analyzed using descriptive statistics and paired sample t-tests. Findings – The study found a significant improvement in vocabulary achievement, with average student scores increasing from 44 (pre-test) to 92 (post-test) (p < 0.05, d = 1.56). The validation of media and materials received high scores (92% and 87%), with 94% positive feedback from teachers. The hybrid method of auditory and physical engagement facilitated better retention in a relaxed learning environment. Novelty – This research contributes by integrating psycholinguistic and kinesthetic methods with a tangible dictionary medium, an approach not explored in previous studies. Significance – The findings benefit elementary educators, curriculum developers, and educational media designers seeking effective tools for enhancing vocabulary acquisition in young learners.